Cement Pond Rice Cultivation for Food Security in Ta Muang Sub-district, Ubon Ratchathani Province - Marnarath, Phengkamon; Tupmongkol, Piyamart (Area Based Development Research Journal, 2023)
Ta Muang sub-district, located in Don Mot Daeng district, Ubon Ratchathani province of Thailand, is known for its high concentration of poverty-stricken households and limited arable land. The primary causes of poverty in this area are recurrent natural disasters, including floods and droughts, which disrupt traditional rice cultivation practices. As a result, local households struggle to produce an adequate food supply, particularly rice, throughout the year. To address these formidable challenges, an innovative approach to rice cultivation in cement ponds has been developed through collaborative efforts of various stakeholders. This method of rice cultivation is resilient to natural disasters and requires minimal land space. The project involves 84 low-income households and comprises eight key activities: 1) Gathering input and feedback from the target low-income households, 2) Allocating the budget for purchasing cement ponds, preparing suitable locations for their placement, and soil preparation for rice cultivation, 3) Conducting field trips to observe experimental rice fields and rice genetic conservation plots, 4) Providing training on rice cultivation techniques to achieve high-quality and maximum yield, 5) Implementing rice cultivation in cement ponds, 6) Promoting the use of organic or Good Agriculture Practices (GAP) methods in rice cultivation within cement ponds, 7) Facilitating knowledge exchange and learning sessions among the target low-income households regarding rice cultivation in cement ponds, and 8) Summarizing the lessons learned from the project. Cement ponds can be installed near the homes of the participating low-income households or in communal areas within the community. This approach does not demand extensive agricultural machinery or a large labor force for maintenance. Moreover, it enables rice harvests at least three times per year, resulting in an estimated production of 96 kilograms of rice per household (equivalent to 60 cement ponds). As a result, participating households can save approximately 2,880 Baht annually. The rice planting project in cement ponds aligns with the development plan of the Tha Muang Subdistrict Administrative Organization, aimed at ensuring food security that is tailored to the conditions, context, and potential of impoverished households.